Neurological Outcomes of Patients With Mycotic Aneurysms in Infective Endocarditis. (January 2021) - Shi, Hang; Parikh, Neal S.; Esenwa, Charles; Zampolin, Richard; Shah, Harsh; Khasiyev, Farid; Valenzuela, Ives; Lavine, Sean; Gutierrez, Jose; Willey, Joshua
Background and Purpose: Mycotic aneurysms (MA) are rare neurovascular complications of infective endocarditis (IE). The natural history and outcomes of MA under contemporary medical therapy have not been well characterized. The purpose of this study is to describe treatments and outcomes of patients with ruptured and unruptured MA in IE, specifically in relation to medical versus surgical/endovascular treatment. Methods: Retrospective chart review was performed at 3 US academic medical centers of adult patients with IE and MA. Information was collected regarding risk factors, imaging, treatments, and outcomes, including ischemic stroke, intracerebral hemorrhage, MA size changes, and inhospital mortality. Results: Thirty-five patients with IE had 63 MA. Nineteen patients had at least one ruptured MA; 13 patients underwent invasive treatment and 6 received antibiotics alone. Of 19 patients on antibiotics alone (6 with at least one ruptured MA and 13 with unruptured MA), 14 underwent repeat imaging and 5 had enlarging MA. Of 16 patients treated invasively, 2 had unruptured MA initially treated with antibiotics but ultimately underwent intervention. No MA ruptured after aneurysm discovery. Fifteen patients underwent cardiothoracic surgery (CTS), of which 11 had unsecured MA and 4 had secured MA. No patients suffered perioperiative neurological events attributable to their MA. Three patients treated with antibiotics alone and 3 patients treated invasively died from causes unrelated to their MAs. Conclusions: For patients with unruptured MA, treatment with antibiotics alone may have similar outcomes to invasive treatment. Further investigation is warranted to determine the risk of undergoing CTS with unsecured MA.